Dana Perlindungan Pemodal: Kajian Hukum Ekonomi Syariah terhadap Pengelolaan, Imbalan dan Jaminan. - Siti Shafa; Isda Maulida; Dwi Aprilianto; Viqram Januar Gawi Kaliky; Jaenudin; Nasih Burhani (TERAJU: Jurnal Syariah dan Hukum, 2026)
The Islamic capital market is experiencing rapid growth, highlighting the importance of the Investor Protection Fund (IPF) as a safeguard mechanism for investors. Specifically, this concerns the clarity of the Wakalah contract regarding remuneration in the management of funds by the IPF, the distribution of remuneration (Ujrah) between the IPF and securities companies, and the proportion of Kafalah and Wakalah. This research was conducted through normative legal research, involving a comprehensive review of the literature, fatwas from the National Sharia Council, and relevant regulations. This method prioritises the application of modern fiqh muamalah rules to DPP practices. The research found that although the concept of DPP is acceptable under positive law, it must be readjusted within the Sharia context. Guarantee mechanisms to ensure compliance must be based on the principle of kafalah or tabarru’, whilst fund management and remuneration must be based on valid contracts such as wakalah bil ujrah. These adjustments are crucial for maintaining investor integrity and trust, and for supporting the growth of a fair and sustainable Islamic capital market.